Diversity and domestication of mushroom species in the Atewa forest reserve and Bia Biosphere, Ghana - Matilda Dzomeku; Francis Alemawor; Jacob K. Agbenorhevi; Ibok N. Oduro; Mary Obodai (Scientific African, 2023)
Edible mushrooms commonly found in forest reserves are important for food security but they are underutilized in Ghana. The Atewa forest reserve in the Eastern Region and Bia Biosphere in the Western Region are among the largest forest reserves in Ghana. However, human activities including illegal mining activities pose a threat to the existence of the rich mushroom diversity within these forests. The objective of this study, therefore, was to collect, characterize and domesticate mushrooms from the Atewa forest reserve and the Bia Biosphere. Wild mushroom samples were randomly photographed, collected, dried and stored. Edible and wild mushrooms were characterized morphologically and compared with literature. A total of 86 mushroom samples (comprising 45 from the Atewa forest reserve and 41 from the Bia Biosphere) were collected and identified. The two forest reserves contained a rich diversity of wild mushrooms namely: Cookeina speciosa, Marasmiellua inoderma, Auricularia cornea, Daldina concentrica, Pleurotus sp. Polypores. Cultivated Auricularia auricula strain AUAT recorded the highest ash content (16.70%) while cultivated Ganoderma sp. strain GLB recorded the lowest ash content (5.12%). On the other hand, cultivated Pleurotus ostreatus strain POB recorded the highest fat content of 19.88% and cultivated Pleurotus saju-caju strain PSCAT gave the least value of 12.02%. Cultivated Auricularia auricula strain AUAT again recorded the highest protein value of 33.38% while wild Ganoderma sp. Strain GLB had the least protein value. A total carbohydrate level of 64.22% was observed in cultivated Ganderma sp. strain GLB. The highest oxalate content of 30.93 mg/100 g was recorded in cultivated Pleurotus ostreatus strain EM1 with cultivated Auricularia auricula strain AUAT being the least value of 4.73 mg. A high phytate value of 149.35 mg was observed in cultivated Auricularia auricula strain AUAT and cultivated Pleurotus saju-caju strain PLAT showed the lowest value of 31.60 mg/100 g. The present findings provide considerable data on fungal diversification, conservation and domestication as well as a reference point for future studies.